Highly Efficient Thermally Activated Delayed Fluorescence Emitter Developed by Replacing Carbazole With 1,3,6,8-Tetramethyl-Carbazole - Cai, Jia-Lin; Liu, Wei; Wang, Kai; Chen, Jia-Xiong; Shi, Yi-Zhong; Zhang, Ming; Zheng, Cai-Jun; Tao, Si-Lu; Zhang, Xiao-Hong (Frontiers in Chemistry, 2019)
Carbazole (Cz) is the one of the most popular electron donors to develop thermally activated delayed fluorescence (TADF) emitters, but additional groups are generally required in the molecules to enhance the steric hindrance between Cz and electron acceptor segments. To address this issue, we replaced Cz with its derivative 1,3,6,8-tetramethyl-carbazole (tMCz) to develop TADF emitters. Two novel compounds, 6-(4-(carbazol-9-yl)phenyl)-2,4-diphenylnicotinonitrile (CzPN) and 2,4-diphenyl-6-(4-(1,3,6,8-tetramethyl-carbazol-9-yl)phenyl)nicotinonitrile (tMCzPN) were designed and synthesized accordingly. With the same and simple molecular framework, tMCzPN successfully exhibits TADF behavior, while CzPN is a non-TADF fluorophor, which is because the additional steric hindrance of methyl groups leads a more twisted structure to tMCzPN. In the organic light-emitting diodes (OLEDs), tMCzPN exhibits extremely high forward-viewing maximum external quantum efficiency of 26.0% without any light out-coupling enhancement, which is significantly higher than that of 5.3% for CzPN. These results indicate tMCzPN is an excellent TADF emitter and prove tMCz is a more appropriate candidate than Cz to develop TADF emitters.